(untitled) (Research, Society and Development, 2020)
This study aimed to analyze the contributions of information and communication technologies (ICT) in the mental health care of health professionals in the context of the COVID-19 pandemic. Descriptive and exploratory research with health professionals assisted by the Center for Integrative and Complementary Health Practices (NUPICS). Data were collected from April to June 2020 through online calls via Instagram’s Center. Bardin’s content analysis was used, elaborating the following categories: exhausting work environment, impaired self-care and importance of the care performed by NUPICS online. The mental health of professionals was compromised, implying physical and psychic symptoms; stress impaired self-care capacity; online care has given way to support through integrative and complementary health practices. ICT was evidenced as fundamental in the mental health care of workers and in the restoration of self-care capacity.